ANALISIS DAMPAK COVID-19 TERHADAP PERTUMBUHAN EKONOMI REGIONAL JAWA TIMUR - Nuraini, Adinda Putri; Suman, Agus (Journal of Development Economic and Social Studies, 2024)
The COVID-19 pandemic has caused the economic growth of East Java to contract. However, not all regions in East Java have experienced a deep contraction. This study aims to estimate the magnitude of the impact of COVID-19 on the regional economic growth of East Java and analyze the impact of COVID-19 on regional growth based on its economic base. This study utilizes the convergence model developed by Barro & Sala-i-Martin, and scatter plot analysis. The results indicate that COVID-19 has caused a contraction in the regional economic growth of East Java through a decrease in sectoral influence. The sector most affected is the mining sector. As a result, spatially, mining areas tend to experience severe contractions, while agricultural areas, which are known for their low prosperity, only experience mild contractions. This condition has contributed to a decrease in the coefficient of interregional inequality in East Java during the pandemic. Considering the importance of the industrial sector in accelerating the resilience of economic growth, an alternative development approach that can be pursued is through the development of agro-industries.